A Ten-Year Retrospective Study on the Clinical and Microbiological Characteristics of Early Onset Neonatal Sepsis at a Single Tertiary Care Institution - Vilma Antonette B Prado; Amanda Louise Du (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Early-onset neonatal sepsis remains a significant cause of morbidity and mortality globally. Although Group B Streptococcus and Escherichia coli were commonly known to be the most common causes of Early-onset neonatal sepsis, this can vary per institution, thus creating a challenge in management. Understanding the clinical and microbiological profile of neonatal sepsis in a single-center study is crucial to improving diagnosis and treatment, strategies. Objectives This study aimed to characterize demographic, clinical, and microbiological features of neonates with early-onset neonatal sepsis, evaluate antimicrobial susceptibility patterns, and assess temporal trends and clinical outcomes over a ten-year period from 2015 to 2024. Methods A retrospective cohort study at a private tertiary hospital included 409 neonates with Early-onset neonatal sepsis. Data on demographics, clinical features, maternal and perinatal risk factors, laboratory results, microbiological findings, antimicrobial susceptibility, and outcomes were collected. Annual trends in culture-positive versus culture-negative cases were analyzed. Statistical tests, including chi-square and t-tests, were utilized. Results Culture-positive neonates had significantly lower birthweight and gestational age, with tachypnea and temperature instability as common signs. The culture-negative group had more asymptomatic cases (20.8% vs 6.3%). Premature rupture of membranes remains the most frequent risk factor. Methicillin-resistant Staphylococcus epidermidis predominated, differing from typical pathogens like Group B Streptococcus. C-reactive protein better distinguished culture-positive sepsis, while leukopenia rather than leukocytosis was a key Complete Blood Count indicator for sepsis. Gram-positive isolates showed high resistance to beta-lactams but remained susceptible to vancomycin and linezolid. Gram-negative isolates were highly susceptible to Amikacin and Piperacillin-tazobactam. Culture-positive sepsis carried a higher mortality (4.2%). Temporal analysis did not exhibit a significant secular trend over the study period. Conclusion Early-onset Neonatal sepsis in this population is marked by vulnerability related to prematurity and low birthweight, diverse clinical presentations, and multidrug-resistant pathogens. Integrated surveillance, tailored antimicrobial stewardship, and targeted preventive strategies are crucial for reducing the sepsis burden and improving neonatal outcomes.